Outcome of adult patients receiving parenteral support at home: 36 years' experience at a tertiary referral centre. Issue 11 (November 2021) - Oke, Siddhartha M.; Nightingale, Jeremy M.; Donnelly, Suzanne C.; Naghibi, Mani; Willsmore, James; Lloyd, David A.J.; Gabe, Simon M.
Summary: Background and aims: Patients with intestinal failure often need long-term home parenteral support (PS). We aimed to determine how the underlying diagnosis, complications and survival had changed over the last 36 years in the UK's largest IF centre. Methods: 978 adult home PS patient records were analysed from January 1979 until October 2016. The age, sex, underlying aetiology, complications and survival was compared over 5-year periods. Results: Pre-1990 to 2011–2016, numbers increased from 29 to 451, the mean age of patients increased from 31 ± 16.5 to 52 ± 17.6 years. The percentage of patients with IF due to surgical complications increased (3.4%–28.8%, p < 0.001)), while those with inflammatory bowel disease decreased (37.9%–22.6%, p < 0.001). Complication of home PS reduced: catheter related blood stream infections (CRBSI) 71.4% to 42, 2%, CVC thrombosis 34.5%–5.3%. Intestinal failure associated liver disease (IFLAD) 10.3%–1.8%. Patients with dysmotility, scleroderma and a congenital aetiology had the highest incidence of CRBSI and CVC Thrombosis. Overall survival was greater pre-1995 [HR 0.2–0.4 (p = 0.02)] most likely associated with an increase in mean age. Survival for patients without malignancy was 90%, 66%, 55%, 45%, 33% and 25% at 1, 5, 10, 15, 20 and 30 years respectively. Multivariate analysis demonstrated a relationship between survival and age of starting home PS; type of home PS; presence or absence of the colon in continuity; and underlying aetiology. Conclusion: Demand for home PS is increasing in particular for advanced malignancy, post-surgical complications and older more co-morbid patients. Complications of home PS are reducing over the last 30 years and 10-year survival for non-malignant aetiologies improving. Survival and changes in aetiology in intestinal failure.